(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The applicability of the two vital formulations (verbaland graphical) of Bradford’s Law of scattering were tested. The study has shownthat the verbal formulation of the present study was closer to the graphicalformulation.